Expression of Calretinin Among Different Neurochemical Classes of Interneuron in the Superficial Dorsal Horn of the Mouse Spinal Cord. (1st February 2019) - Gutierrez-Mecinas, Maria; Davis, Olivia; Polgár, Erika; Shahzad, Mahvish; Navarro-Batista, Keila; Furuta, Takahiro; Watanabe, Masahiko; Hughes, David I.; Todd, Andrew J.
Highlights: Calretinin is differentially expressed among excitatory interneurons in the superficial dorsal horn of mouse spinal cord. Calretinin is present in many excitatory interneurons that express neurokinin B, substance P or gastrin-releasing peptide. Consistent with recent transcriptomic data, we find that most inhibitory substance P-expressing neurons contain calretinin. Abstract: Around 75% of neurons in laminae I-II of the mouse dorsal horn are excitatory interneurons, and these are required for normal pain perception. We have shown that four largely non-overlapping excitatory interneuron populations can be defined by expression of the neuropeptides neurotensin, neurokinin B (NKB), gastrin-releasing peptide (GRP) and substance P. In addition, we recently identified a population of excitatory interneurons in glabrous skin territory that express dynorphin. The calcium-binding protein calretinin is present in many excitatory neurons in this region, but we know little about its relation to these neuropeptide markers. Here we show that calretinin is differentially expressed, being present in the majority of substance P-, GRP- and NKB-expressing cells, but not in the neurotensin or dynorphin cells. Calretinin-positive cells have been implicated in detection of noxious mechanical stimuli, but are not required for tactile allodynia after neuropathic pain. Our findings are therefore consistent with the suggestion that neuropathic allodynia involves the neurotensin and/or dynorphin excitatory interneuron populations. Around a quarter of inhibitory interneurons in lamina I-II contain calretinin, and recent transcriptomic studies suggest that these co-express substance P. We confirm this, by showing that inhibitory Cre-expressing cells in a Tac1 Cre knock-in mouse are calretinin-immunoreactive. Interestingly, there is evidence that these cells express low levels of peptidylglycine alpha-amidating monooxygenase, an enzyme required for maturation of neuropeptides. This may explain our previous finding that although the substance P precursor preprotachykinin A can be detected in some inhibitory interneurons, very few inhibitory axonal boutons are immunoreactive for substance P.